Estudo comparativo, randomizado para avaliar a eficácia terapêutica da Mentha crispa e do secnidazol no tratamento da tricomoníase - Cavalcanti, Pacífica Pinheiro (2010)
Trichomoniasis is a non-viral sexually transmitted disease most common in the world. The current treatment of this disease includes the use of several drugs, including herbal remedies formulated with Mentha crispa have also been used as protozoan The aim of this study was to evaluate the efficacy and safety of herbal medicine containing Mentha crispa in patients with vaginal trichomoniasis. The study was a randomized clinical trial, parallel and opened. It included 60 female volunteers, 35 from Fortaleza - Ceara and 25 from Sinop - Mato Grosso, who had stool examination of vaginal discharge positive for trichomoniasis. Patients were randomly distributed in two treatment groups, the Mentha crispa group and the Secnidazole group. Both groups were composed of 30 volunteers, in which, respectively, 2 tablets of 12 mg of herbal Giamebil® and 2 tablets 1000mg Secnidal ® were orally administered in single dose. The clinical trial consisted of three steps: pretreatment, treatment and post-treatment. To significance level of 5%, no difference was found between the groups (P = 0.6120), because the proportion of volunteers with no T.vaginalis in the Secnidazole group was 96.67% and the proportion found in the Mentha crispa group was 90.00%. Secondary endpoints for the evaluation of the effectiveness of Mentha crispa in the treatment of trichomoniasis were the improvement of clinical complaints: vaginal discharge, unpleasant odor, genital burning, dysuria, dyspareunia, pelvic pain and itching. It has not been demonstrated statistically significant difference (P = 0 , 4583) between the treatments in the proportion of patients who reported no such complaints. The drugs were considered well tolerated, as no voluntary needed additional pharmacological intervention in order to control or eradicate such discomfort. Therefore, adverse events were assessed as being mild, manifesting itself only once and having spontaneous remission. However, adverse effects were significantly higher (P = 0.0006) in the Secnidazole group (66.67%) than those found in the Mentha crispa group (20.00%). Adverse events reported by volunteers Secnidazole group were nausea (16.67%), the unpleasant odor in the urine (3.33%) and metallic taste, that was cited by 50% of patients and it showed a statistically significant difference between the treatment groups (P <0.001). The referred events by the volunteers of the Mentha crispa group were: epigastric pain, nausea, vomiting and headache reported by 3.33%, while unpleasant taste was mentioned by 6.67%. No signs of clinical toxicity was observed during treatment. This trial concluded that the herbal medicine containing Mentha crispa showed efficacy and safety when used orally at a dose of 24mg, presenting itself as an alternative therapy safe, effective, accessible and with quality for treatment in patients with trichomoniasis.